2001
DOI: 10.1086/319203
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Pulmonary and Disseminated Coccidioidomycosis: Kern County, California, 1995-1996

Abstract: Surveillance for coccidioidomycosis (CM) and a case-control study for risk factors among adults were conducted in Kern County, California. From January 1995 through December 1996, 905 cases of CM were identified, for an annual incidence of 86 cases per 100,000 population. A total of 380 adults were enrolled in the case-control study: 77 had severe pulmonary disease, 33 had disseminated disease, and 270 control patients had mild disease. Independent risk factors for severe pulmonary disease included diabetes, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
1
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(163 citation statements)
references
References 24 publications
9
140
1
7
Order By: Relevance
“…40 More recently, population-based studies of coccidioidomycosis in Kern County, California, in 1991 32 and in 1995 to 1996 41 showed that blacks had a disproportionate percentage of disseminated infection (31% of all disseminated cases were in blacks, but blacks accounted for only 6.7% of all coccidioidal infections 32 ) and an increased rate of dissemination (22%), whereas a similar increase in dissemination was not noted for Hispanic or Asian patients. 32,41 Among 223 patients at Naval Medical Center San Diego (1994-2002), 44% of African American patients with coccidioidomycosis had extrapulmonary infection, and the risk of disseminated disease was 42 times higher in African Americans than in whites (the risk of disseminated disease in Filipinos and Hispanics was also significantly higher). 24 A small study of 59 active duty military personnel at Naval Air Station Lemoore did not find a statistically increased risk of dissemination among African Americans compared with whites, but 6 African Americans had coccidioidomycosis, 2 of whom had disseminated infection.…”
Section: Risk Of Disseminationmentioning
confidence: 99%
“…40 More recently, population-based studies of coccidioidomycosis in Kern County, California, in 1991 32 and in 1995 to 1996 41 showed that blacks had a disproportionate percentage of disseminated infection (31% of all disseminated cases were in blacks, but blacks accounted for only 6.7% of all coccidioidal infections 32 ) and an increased rate of dissemination (22%), whereas a similar increase in dissemination was not noted for Hispanic or Asian patients. 32,41 Among 223 patients at Naval Medical Center San Diego (1994-2002), 44% of African American patients with coccidioidomycosis had extrapulmonary infection, and the risk of disseminated disease was 42 times higher in African Americans than in whites (the risk of disseminated disease in Filipinos and Hispanics was also significantly higher). 24 A small study of 59 active duty military personnel at Naval Air Station Lemoore did not find a statistically increased risk of dissemination among African Americans compared with whites, but 6 African Americans had coccidioidomycosis, 2 of whom had disseminated infection.…”
Section: Risk Of Disseminationmentioning
confidence: 99%
“…Underlying pathogen or host genetic factors that lead to a greater proportion of milder or subclinical cases may account for this phenomenon. In coccidioidomycosis, being of Filipino descent has been associated with a greater risk for dissemination, 23 suggesting that host factors can indeed play a role in the manifestation of endemic fungal infections. Alternatively, histoplasmosis may be misdiagnosed as other chronic granulomatous diseases such as TB or dimorphic fungal infections or simply underreported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the large influx of elderly individuals to Arizona from non-endemic areas may explain their disproportionate burden of disease given that the incidence of infection within California peaks between 40 and 49 years of age [23]. Two studies to evaluate for poor outcomes or severe, disseminated disease were not able to conclusively identify age as a risk factor [24,25]. While coccidioidomycosis affects all age groups, adults are identified as the most affected group.…”
Section: Agementioning
confidence: 99%
“…Acute pulmonary disease in African Americans compared to Caucasians was documented at a rate of 67 vs. 19 per 100,000 while disseminated disease was noted in 23.8 vs. 2.5 per 100,000. In addition to Blacks, people of Asian and Filipino descent are also thought to be at disproportionate risk for disseminated disease [25]. The reasons for ethnic variations for Coccidioides infection are not entirely clear but are likely to be explained by immunogenetic differences in T cell function.…”
Section: Ethnicitymentioning
confidence: 99%